Development and validation of self-reported line drawings of the modified Beighton score for the assessment of generalised joint hypermobility - Cooper, Dale J.; Scammell, Brigitte E.; Batt, Mark E.; Palmer, Debbie (BioMed Central, 2018)
Background: The impracticalities and comparative expense of carrying out a clinical assessment is an obstacle in many large epidemiological studies. The purpose of this study was to develop and validate a series of electronic self-reported line drawing instruments based on the modified Beighton scoring system for the assessment of self-reported generalised joint hypermobility. Methods: Five sets of line drawings were created to depict the 9-point Beighton score criteria. Each instrument consisted of an explanatory question whereby participants were asked to select the line drawing which best represented their joints. Fifty participants completed the self-report online instrument on two occasions, before attending a clinical assessment. A blinded expert clinical observer then assessed participants’ on two occasions, using a standardised goniometry measurement protocol. Validity of the instrument was assessed by participant-observer agreement and reliability by participant repeatability and observer repeatability using unweighted Cohen’s kappa (k). Validity and reliability were assessed for each item in the self-reported instrument separately, and for the sum of the total scores. An aggregate score for generalised joint hypermobility was determined based on a Beighton score of 4 or more out of 9. Results: Observer-repeatability between the two clinical assessments demonstrated perfect agreement (k 1.00; 95% CI 1.00, 1.00). Self-reported participant-repeatability was lower but it was still excellent (k 0.91; 95% CI 0.74, 1.00). The participant-observer agreement was excellent (k 0.96; 95% CI 0.87, 1.00). Validity was excellent for the self-report instrument, with a good sensitivity of 0.87 (95% CI 0.81, 0.91) and excellent specificity of 0.99 (95% CI 0.98, 1.00). Conclusions: The self-reported instrument provides a valid and reliable assessment of the presence of generalised joint hypermobility and may have practical use in epidemiological studies.